Equus - Leow, Puay Tin *; Teoh, Melissa * (Sunway University. Dept. of Performance & Media, 2008)
In Peter Shaffer's Equus, a stable-boy who loves horses passionately suddenly blinds six horses with a metal spike one night. Everyone including his parents, is shocked by the violence of his act. Refusing to give up on him, his psychiatrist works like a detective to uncover the events that let to that terrible crime.